THE EFFECT OF WEBTOON ON STUDENTS’ ENGLISH VOCABULARY AT SMK NEGERI 1 PALANGKA RAYA - Mirandae Feronika; Riskiati Rasya; Intan Meitri Nadia; Maria Arina Luardini (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This study investigated the effect of Webtoon for students’ English vocabulary. Quantitative research with quasi-experimental design is the method that was used for this study. The population of this study is students of SMK Negeri 1 Palangka Raya. The sample was selected by using total sampling, consisting of 14 ten grade students of Teknik Konstruksi Perumahan (TKP) class. In collecting the data, the researchers used pre-test and post-test. Meanwhile, the researchers used Pearson Correlation to analyze the data statistically. According to the result of the study, Webtoon showed a significant effect on students’ vocabulary. A combination of engaging narrative and unique illustration helped the process of learning new vocabulary to be more enjoyable.